2013
DOI: 10.7727/wimj.2006.135
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Exertional Anterior Compartment Syndrome of the Leg

Abstract: Exertional leg pain is a common presenting complaint of athletes to sports physicians and physiotherapists. Careful analysis can lead to an accurate diagnosis and commencement of effective treatment. Exertional anterior compartment syndrome can be successfully treated utilizing a closed fasciotomy with a rapid return to sport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Improvement of symptoms or satisfaction was reported by 47% (±42%) of the patients who completed a follow-up analysis, whereas 50% (±45%) returned to a form of physical activity. The well-structured gait retraining programs 20,23 and treatment with botulinum injections 22 scored highest with satisfaction rates ranging from 89% to 100%, whereas all studies with patients alone initiated modifications in activity and/or lifestyle 7,8,[24][25][26][27] scored between 0% and 84% satisfaction. Among the 171 conservatively treated patients, six cases were reported to eventually opt for surgery.…”
Section: Outcome Following Conservative Treatmentmentioning
confidence: 99%
“…Improvement of symptoms or satisfaction was reported by 47% (±42%) of the patients who completed a follow-up analysis, whereas 50% (±45%) returned to a form of physical activity. The well-structured gait retraining programs 20,23 and treatment with botulinum injections 22 scored highest with satisfaction rates ranging from 89% to 100%, whereas all studies with patients alone initiated modifications in activity and/or lifestyle 7,8,[24][25][26][27] scored between 0% and 84% satisfaction. Among the 171 conservatively treated patients, six cases were reported to eventually opt for surgery.…”
Section: Outcome Following Conservative Treatmentmentioning
confidence: 99%
“…This cohort study compares treatment outcome as reflected by changes in cardinal symptoms, patient satisfaction, as well as return to physical activity. Similar differences in satisfaction favoring surgery were already demonstrated in most small cohorts [6,8,22,23]. However, an exact description of the methodology for determining satisfaction was often lacking.…”
Section: Discussionmentioning
confidence: 61%
“…The three different types of lower leg CECS, including combinations, were not separately evaluated. Our study design is different from previously published cohorts focusing on the anterior compartment only [22][23][24]. For instance, the study by Packer et al [23] found higher satisfaction rates in patients only receiving a fasciotomy for the anterior compartment compared to patients undergoing surgery for multiple compartments.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Cases required the following: symptoms of exercise-induced leg pain consistent with a diagnosis of anterior compartment CECS; no diagnosis other than CECS more likely; absence of multiple lower limb pathologies; and, no previous lower limb surgery. While intramuscular compartment pressure measurement is considered the gold standard for diagnosis (Roscoe, Roberts, & Hulse, 2015); clinical examination alone has been suggested to provide an accurate diagnosis for referral for surgery (Ali et al, 2013, Orlin, Oen, & Andersen, 2013, van den Brand et al, 2005. As pressure measurement was not available for this study, a clinical diagnosis was used.…”
Section: Methodsmentioning
confidence: 99%